2022
DOI: 10.1002/advs.202201144
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Rainfall Patterns Constrain the Multidimensional Rewilding of Global Forests

Abstract: The long-term contribution of global forest restoration to support multiple dimensions of biodiversity and ecosystem function remains largely illusive across contrasting climates and forest types. This hampers the capacity to predict the future of forest rewilding under changing global climates. Here, 120 studies are synthesized across five continents, and it is found that forest restoration promotes multiple dimensions of biodiversity and ecosystem function such as soil fertility, plant biomass, microbial hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
(90 reference statements)
2
26
0
Order By: Relevance
“…Grand mean of RR was calculated using weighted mean of RR using the equation:italicRRggoodbreak=)(italicni*italicRRiitalicni where RRg is the grand response ratio of soil N 2 O emissions across all studies, RRi the response ratio of soil N 2 O emission from the i th meta‐analysis study (paper), and n i the sample size. We took a conservative approach and used the sample size as weight rather than the reverse of variance, as differences in variance, especially some small variances may create heavy weights on a few studies (Eldridge et al, 2016; Sánchez‐Meca & Marin‐Martinez, 1998; Zhou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Grand mean of RR was calculated using weighted mean of RR using the equation:italicRRggoodbreak=)(italicni*italicRRiitalicni where RRg is the grand response ratio of soil N 2 O emissions across all studies, RRi the response ratio of soil N 2 O emission from the i th meta‐analysis study (paper), and n i the sample size. We took a conservative approach and used the sample size as weight rather than the reverse of variance, as differences in variance, especially some small variances may create heavy weights on a few studies (Eldridge et al, 2016; Sánchez‐Meca & Marin‐Martinez, 1998; Zhou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Ecosystem multifunctionality (EMF) index has been increasingly considered as a reliable indicator reflecting the effects of climate change and anthropogenic activity on multiple ecosystem functions (Z. C. Zhang et al, 2021; Zhou et al, 2022). Reports had showed that reseeding could greatly affect multiple ecosystem functions in alpine meadows such as plant diversity, productivity, and soil physical and chemical properties (Gou et al, 2019; Li et al, 2021; L. Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By slowing down the rate of SOC mineralization and increasing SOC content, it is possible to reduce the release of CO 2 into the atmosphere and maintain soil health. To date, our understanding of how ecological restoration affects SOC mineralization and its mechanism in alpine grasslands lags considerably behind that of SOC storage ( Zhou et al, 2022 ). These knowledge gaps undermine our predictions of ecological restoration effects on soil C processes and constrain the improvement of restoration management practices to resist land degradation.…”
Section: Introductionmentioning
confidence: 99%